Assessment tools instruments for diagnostics of the intensive care unit acquired weakness: Narrative review (Research, Society and Development, 2021)
Introduction: the intensive care unit acquired weakness (ICUAW) is a common condition in patients of the intensive care unit (ICU) due to inactivity, mechanical ventilation, use of neuromuscular blocker, chock, sepsis, renal failure and hyperglycemia. The ICUAW is identified by the overall reduction of the muscle strength, this affects in symmetrical ways the peripheral and respiratory muscle. Objective: verify the principals evaluation tools for the diagnostic of the ICUAW and available treatments. Methodology: review of narrative literature, through researches in the data base of Lilacs, Medline y PubMed, with studies between the years of 2016 until 2020. Results:  originally were identified 8887 papers, where 838 were excluded by the reading of the summary and title, 49 papers were read in full and 15 more that attempted the criteria were included in this review, 8 treated about the diagnosis and 7 in respect of the ICUAW treatment in the ICU. Conclusion: the ICUAW is often experienced in critical patients kept in rest, the most used tolls for the diagnostic were the Medical Research Council (MRC), dynamometer and the ultrasound examination. The early mobilization is considered an improvement tool for the recovery of the critical sick, therefore is a secure and viable option for the treatment.